Themes in published obituaries of people who have died of opioid overdose. Issue 3 (2nd October 2018) - Rajesh, Kavya; Crijns, Tom J.; Ring, David
Abstract: This study gauged public perceptions of the opioid epidemic in online obituaries related to opioid overdose by analyzing emotional themes and tones. A thematic analysis was performed on a consecutive listing of online obituaries from the United States. Three hundred electronic obituaries of people who died due to opioid, heroin, and prescription drug overdose, identified in an online obituary platform (Legacy.com) using the keyword "overdose" were used. Tones, emotions, terms used to describe death, and types of opioids were measured using the string search function of Stata and IBM Watson Tone Analyzer. Our analysis showed that joy and sadness are the most prevalent tones in these obituaries (92% and 88%, respectively) and the most common emotion was love (79%). The two most commonly used terms to describe death due to opioid overdose were 'accidental' (53%) and 'addiction' (34%). The two types of narcotics named were 'heroin' (35%) and 'prescription opioids' (7.8%). Obituaries of people who have died due to opioid overdose contain main themes of love, joy, and sadness. The fact that stigma and shame were less prevalent themes might suggest support of the concept that addiction should be regarded as a disease rather than a criminal behavior.